Strategic Credit Policy Adjustments During Economic Shocks: Lessons From Indonesia’s Manufacturing Sector - Fenty Fauziah; Siti Rosa Lismawati; Nur Hanisfatin Rushami Zien (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Receivables management is a critical component of working capital strategy, particularly during periods of economic disruption. The COVID-19 pandemic posed liquidity challenges for manufacturing firms, testing the balance between RTO, ACP, and profitability.Purpose: This study investigates the effects of Receivables Turnover (RTO) and Average Collection Period (ACP) on the profitability of manufacturing firms in Indonesia, measured by Return on Assets (ROA), during the COVID-19 crisis and post-pandemic recovery.Design/methodology/approach: Using panel data from 167 manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2023, this research applies panel data regression to analyze the relationship between receivables indicators and firm profitability.Findings/Results: The analysis shows that higher RTO is positively associated with ROA, indicating enhanced profitability through efficient cash recovery. Conversely, longer ACP negatively impacts ROA. However, in 2020, firms strategically extended ACP to support customer relationships, which, while reducing short-term returns, improved performance in the recovery years.Conclusion: Credit policies serve a dual function: enhancing liquidity and fostering customer retention. Flexible receivables strategies can buffer firms during crises and position them for post-crisis resilience.Originality/value (State of the art): This study offers timely insights into how receivables management can be leveraged as a strategic response to economic shocks in emerging markets. Keywords: profitability, receivables turnover, average collection period, credit policy, economic shocks